Exploring the Effect of Enzyme and Protein-Containing Toothpaste on Gum Health: A Systematic Review - Silvia D’Agostino; Marco Dolci (Microorganisms)
This systematic review critically evaluates the efficacy of enzyme- and protein-containing toothpastes in augmenting saliva’s inherent protective mechanisms. Adhering to PRISMA guidelines and having been registered under PROSPERO (CRD42024558854), a comprehensive literature search was conducted across PubMed, Web of Science, and Scopus, employing a PICO-structured query with the MeSH terms “enzymes”, “proteins”, and “toothpaste”. The inclusion criteria were restricted to in vivo human studies, published in English within the last 10 years, assessing the gingival effects of these toothpastes. Risk of bias was assessed using the Cochrane RoB 2.0 for randomized controlled trials (RCTs) and ROBINS-I for non-randomized controlled trials (N-RCTs). From an initial pool of 62 articles, three studies met the inclusion criteria: two RCTs exhibiting low to medium risk of bias and one N-RCT with low risk of bias. The analysis suggests that enzyme- and protein-enriched toothpastes may contribute to improved gingival health following 12 weeks and 12 months of use. However, the hypothesized effect against extrinsic black stains was not substantiated within the selected studies. These findings, while promising, are constrained by the limited number of included studies, necessitating further investigations to validate these observations and explore the broader implications of enzyme- and protein-based oral care formulations.